2018
DOI: 10.1111/jofo.12268
|View full text |Cite
|
Sign up to set email alerts
|

Estimates of wear rates in metal bird bands, with applications for survival and movement models of marked individuals

Abstract: Banding allows identification of individual birds, and many investigators use data from recaptured or recovered birds to infer population parameters, including survival rates, migration rates, and recruitment rates. Such analyses often assume that band loss is negligible, but wear rates have been found to differ markedly among different band sizes, band metals, and species in the few cases where wear rates have been determined. However, rapidly wearing bands may be over‐reported in the published literature rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…The rates of ring wear and loss may vary among and within species depending on behaviour and habitat (Harris 1980). Rates of ring wear or loss may also depend on the material used or the background colour of the ring, for example plastic colour-rings generally wear at faster rates than steel or aluminium rings (Koronkiewicz et al 2005;Sandvik et al 2005;Baylis et al 2018). Darvic colour-rings have been recommended for shorebird studies in recent years, which are made from a pressed PVCU sheet and is colour-fast, hard wearing and malleable (Ward 2000;Robinson et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The rates of ring wear and loss may vary among and within species depending on behaviour and habitat (Harris 1980). Rates of ring wear or loss may also depend on the material used or the background colour of the ring, for example plastic colour-rings generally wear at faster rates than steel or aluminium rings (Koronkiewicz et al 2005;Sandvik et al 2005;Baylis et al 2018). Darvic colour-rings have been recommended for shorebird studies in recent years, which are made from a pressed PVCU sheet and is colour-fast, hard wearing and malleable (Ward 2000;Robinson et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…While an aluminium ring worn by a common raven (Corvus corax) for 41 months may still appear legible in a photograph, these birds may lose aluminium rings through wear after 10 to 15 years (Bedrosian & Craighead, 2007). Aluminium rings on passerines wear at about 3% of their mass per year (Baylis et al, 2018), and judging from my photographs, the mass loss of the ring on the bird being studied is not less than 30%. Therefore, assuming a comparable ringing date (about 10 years before my observation), my first explanation would have been unlikely.…”
Section: Introductionmentioning
confidence: 79%
“…Additionally, a post hoc review of our data shows that the average number of years between banding and recovery for doublebands from both lesser scaup and redheads was almost identical whether hunters sent them to us for evaluation or chose not to participate. Baylis et al (2018) suggest that studies motivated by observed excessive band wear can overestimate band wear as an overall problem. However, as we observed, loss of contact information influences the likelihood of return once recovered and could result in samples being biased toward recovered bands that are more legible, depending on the species of focus.…”
Section: Discussionmentioning
confidence: 99%
“…Baylis et al (2018) suggest that studies motivated by observed excessive band wear can overestimate band wear as an overall problem. However, as we observed, loss of contact information influences the likelihood of return once recovered and could result in samples being biased toward recovered bands that are more legible, depending on the species of focus.…”
Section: Discussionmentioning
confidence: 99%